Navigating role conflicts and responsibilities in higher education for sustainable development: insights from German university teachers - Schlieszus, Ann-Kathrin; Weselek, Johanna; Siegmund, Alexander (Gaia, 2024)
Higher education for sustainable development can be a challenge for university teachers, as the concept’s normativity may contrast with their self-perception as neutral researchers and teachers. Based on an interview study, the authors examine three role conflicts which may occur - in higher education for sustainable development and offer perspectives on how these may turn into learning opportunities.Higher education for sustainable development (HESD) can be challenging for university teachers. The normative core of the concept may be perceived as a contrast to the - ideal of objective knowledge production which has dominated Western academia for a long time. As university teachers concurrently fulfil different roles, they can be exposed to sometimes incompatible expectations. In this paper, we present role conflicts university teachers may face when implementing - ESD in their courses. For this, we used sociological role theory as a framework to analyse data from a qualitative interview study conducted with university teachers. The results show three typical role conflicts: 1. the “personal stance” conflict, 2. the “practice what you - preach” conflict, and 3. the “lethargic institution” conflict. In order to support university teachers in coping with these conflicts, we recommend reflecting on ESD-related values and ambiguities in university classes, reinforcing professional development for university - teachers in ESD, especially in the field of emotional competence, and the implementation of Whole Institution Approaches.
Veröffentlichungsdatum: 30 Dezember 2024
Gesehen am 16.06.2025